Disciplined Behaviour And Students’ Responsibility Through The Role Of The Classroom Environment: A Qualitative Study - Rino, Pitaloka Pasha; Setiawan, Deni (JTP - Jurnal Teknologi Pendidikan, 2025)
The classroom environment plays a central role in shaping the disciplined behaviour and responsibility of primary school students. Discipline reflects students' adherence to classroom rules, while responsibility relates to their awareness in completing tasks and accepting the consequences of their actions. This study aims to analyse how the classroom environment, both physical and social aspects, contributes to the development of disciplined behaviour and responsibility among Year 5 students at Wonolopo 03 Elementary School. The research employs a qualitative approach using interviews, observations, and documentation techniques. The findings indicate that a well-organised classroom environment, supported by mutually agreed-upon rules and positive social interactions, can enhance students' discipline and sense of responsibility. However, several challenges exist, such as differences in students' characters, external environmental influences, and difficulties in enforcing rules. Teachers implement strategies such as habituation, clear consequences, and effective communication to address these challenges.